Seismogeological section of the Earth's crust of North Karelia along the profile of Kandalaksha - Kem - N. V. Sharov; A. I. Slabunov; E.V. Isanina; N. A. Krupnov; V. I. Pozhilenko; V. A. Rakitov (Геофизический журнал, 2013)
CDP, DSS and seismotomographic section along the North Karelian portion of geotraverse 1-ЕВ (Kandalaksha - Kem) have made it possible for the first time to study in detail the earth crust under the Belomorian province within the limits of the Phenno-Scandian Shield. Correlation and integrated interpretation of CDP time sections, DSS multi-wave sections and geological data show that the results obtained by the seismic methods differ markedly, but the data obtained by both methods are important for geological interpretation because they emphasize different environmental characteristics. Tectonic dislocation zones, extending to M-discontinu-ity, were delineated and traced downwards. The crystalline crust of the Belomorian province was shown to have a nappe tectonics. Horizontal variation in velocity correlates with heterogeneities in crustal section responsible for its blocky geological structure. The heterogeneity pattern of the crust seems to reflect collision tectonics, and as a result tectonic slits of different composition were superposed.